Enhancing postoperative analgesia in carotid endarterectomy patients: The potential of ultrasound-guided carotid sheath block combined with superficial cervical plexus block: A randomised trial - Anamarija Kruc; Lada Lijovic; Matteo Skrtic; Iva Pazur; Nikola Perisa; Tomislav Radocaj (Indian Journal of Anaesthesia)
Background and Aims: Carotid endarterectomy (CEA) is a common procedure conducted under regional anaesthesia, providing real-time cerebral function monitoring. Many different combinations of regional cervical blocks exist, and most offer adequate analgesia in intraoperative and postoperative recovery. This research compares a superficial cervical plexus block (SCB) alone and combined with an ultrasound (US)-guided carotid sheath block (CSB). The primary objective was to explore the length of the sensory block after combining SCB and CSB. Methods: Patients scheduled for nonemergency CEA surgery were randomised into two cohorts. The Subject group (28 participants) received US-guided CSB and SCB. The Control group (31 participants) received only an SCB. Both groups received 0.5% levobupivacaine (2 mg/kg) along with 2% lidocaine (2 mg/kg). The sensory block time and its initiation, analgesia and neutrophil-to-lymphocyte ratio (NLR) were recorded before and after the block. The numeric pain rating scale (NPRS) was used to evaluate analgesia every 2 h for 12 h post block. Analysis of variance, Mann–Whitney U or log-rank test was used to analyse the distinction of selected variables. Results: The demographic characteristics were comparable across the cohorts. The Subject group demonstrated a significantly accelerated onset of sensory block (P = 0.029) and an extended time to first analgesia (P = 0.003). The sensory block was also substantially extended in the Subject group (P = 0.040). Postoperative pain (NPRS ≥1) within the first 12 h was more recurrent in the Control group (P = 0.048). NLR showed minimal disparity between the groups (P = 0.125). Conclusion: Combining SCB and US-guided CSB effectively and safely extends postoperative analgesia for CEA surgery.